Saer’s painting - Scavino, Dardo (Letras, 2024)
In La mayor(1975), Juan José Saer described Van Gogh’s Wheatfield with Crows. In Glosa (1986), he did the same with a dripping of an imaginary artist, Rita Fonseca, a Santa Fe transfiguration of Jackson Pollock. In our article, we intend to show that through these descriptions Saer revealed the mutations of his aesthetics before and after El entenado (1980).